GAYA KEPEMIMPINAN TRANSFORMASIONAL DALAM HUBUNGAN SISTEM PENGENDALIAN INTERN DAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada SKPD Provinsi Bali) - Pradipa, Nyoman Angga; Dwija Putri, IGAM Asri; Ratnadi, Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
The objective of this study is to determine the effect of intern control system, the transformational leadership style, and their interaction on the quality of financial statements. The data collection method is questionnaire technique. The number of samples were 91 employees in regional work unit in Bali Province that selected based on proportionate stratified random sampling method. This study used a quantitative analytical approach, that is Structural Equation Modeling (SEM) with the calculation process assisted by application programs Partial Least Square (PLS). The result shows that the intern control system more effectively and implementation of transformational leadership style causes improvement to the quality of financial statements. The transformational leadership style is not a moderating variable in relation to the internal control system and the quality of government financial statements.
Keywords: quality of financial statements, intern control system, transformational leadership style, regional work unit in Bali Province.